Do different ADHD‐related etiological risks involve specific neuropsychological pathways? An analysis of mediation processes by inhibitory control and delay aversion. (2nd March 2013) - Pauli‐Pott, Ursula; Dalir, Silke; Mingebach, Tanja; Roller, Alisa; Becker, Katja
<x xml:space="preserve">Abstract</x> Background Inhibitory control (IC) has been regarded as a neuropsychological basic deficit and as an endophenotype of attention deficit/hyperactivity disorder (ADHD). Implicated here are mediation processes between etiological factors and ADHD symptoms. We thus analyze whether and to what extent executive IC and delay aversion (DA; i.e., reward‐related IC) performance mediate the associations of familial, prenatal, and psychosocial risks with ADHD symptoms. Methods The study sample consisted of 130 preschool children (3–6 years; 50% boys), including 20% (n = 26) with a positive family history of ADHD (familial risk). Prenatal risks were mainly taken from medical records. Psychosocial risks were assessed by a structured interview. ADHD symptoms were assessed by structured interviews and questionnaires completed by parents and teachers. A set of neuropsychological tasks on IC and DA was conducted with the children. Results Familial, prenatal, and psychosocial risks were significantly associated with ADHD symptoms. IC and DA also correlated significantly with ADHD symptoms. While the familial risk significantly correlated with IC and DA, psychosocial and prenatal risks were only weakly associated with these measures. The link between the familial risk and ADHD symptoms was partially mediated by IC and DA. Conclusions The results indicate different neuropsychological pathways related to 'positive family history of ADHD' and prenatal risks. Given a cross‐validation in future studies, the results underscore the endophenotypic character of IC and DA in preschool ages.